(untitled) (Research, Society and Development, 2022)
Orotracheal intubation (OTI) is a medical, invasive and advanced support procedure that aims to establish airway control. The performance of this procedure is more common in patients in operating rooms, in the Intensive Care Unit - ICU and in the emergency room. The procedure needs some care to minimize complications, since intubation is performed by handling the orotracheal tube to keep the route open and can cause laryngeal edema in most patients, vocal cord injury, ulceration and some effects such as nausea, vomiting and arrhythmias. Based on this principle, the objective of this study focuses on: Identifying from the literature, essential clinical practices to minimize complications during orotracheal intubation procedures. This is a systematic literature review, carried out through a survey in the following databases: LILACS, BDENF and BRISA. The results indicate that orotracheal intubation emerges from a variety of care that must be followed by the team, being essential to obtain maximum success in the first attempt of laryngoscopy. Knowing that the procedure can cause some side effects to the patient, such as vocal cord injury, ulcerations and edema, the team must always be aware of the need for fluid drainage, preventing fluid retention, preventing the risks of aspiration/regurgitation, monitoring cuff pressure, perform oral hygiene daily, keep the head high, prevent respiratory infections and constantly change the humidifiers of the mechanical ventilator.